Crossing… transatlantic cycles: dramaturgy, Candomblé and ritual - Ferreira, Tássio (Revista Brasileira de Estudos da Presença, 2023)
The present work reflects on the expanded dramaturgical conception of an acting black poetics entitled Afrocênica, immersed in the AFRO(en)CENA Collective, through the scenic experiment Travessias… ciclos transatlânticos. The concept of expression in the ritual scene is discussed, outlining the notion of a dramaturgy in cycles, inspired by the worldview of Candomblé Congo-Angola. It is intended to contribute to the expansion of epistemologies within the scope of black performance, especially in the investment in new scenic writings that take into consideration the horizontality of the black scene based on the traditional social ritual production of the Bantu.